ANALISIS SIMULASI KEGAWAT DARURATAN KORBAN TENGGELAM TERHADAP KETERAMPILAN MANAGEMENT OF DROWNING PEMUDA AREA BENDUNGAN NIAMA: Analysis of Emergency Simulation of Drowning Victims of Youth Management of Drowning Skills In The Niama Dam Area - Zuniawati, Dewi; Pringgotomo , Gathut; Nizar, Angga Miftakhul (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2023)
Drowning is dangerous and can result in death in less than 24 hours. A drowning victim is an emergency that needs immediate treatment. The purpose of this study was to analyze the emergency simulation of drowning victims on the skills of management of drowning in youth in the Niama Dam Area. The research design used is a quasy experiment with a one-group pre-post test design approach. The research sample was some of the youth on the banks of the Niama Dam who were there at the time of the research with 30 respondents who were selected using a purposive sampling technique. The results of this study indicate that most of the respondents had a moderate skill level before being given an emergency simulation with a total of 13 respondents (43%). Meanwhile, after being given an emergency simulation, most of the respondents had a good skill level with a total of 19 respondents (63%). This study proves the simulation of the emergency for drowning victims on skills about management of drowning in youth in the Niama Dam Area. Keywords: Drowning, Emergency Simulation, Nursing